The CLIL Concept - Novelty or Routine for Primary Teachers in Slovenia: A Case Study - Saša Jazbec; Metka Lovrin (University of Maribor Press, 2015)
CLIL (Content and Language Integrated Learning) is a modern didactical concept of learning and teaching foreign languages. The approach is multifaceted, and known under different names (language bath, non-linguistic subject in a foreign language, bilingual education and immersion) and different forms of implementation. CLIL is slowly becoming a part of the Slovene educational system. It is recommended in curricula; linguistics students, students of primary teacher education, students of preschool education and teachers of similar profiles discover, study and investigate it. The aim of the theoretical part of the article is to present CLIL and its projects-milestones in the process of implementing the concept-whereas the empirical part deals with the results of a qualitative research study in which teachers were interviewed in order to establish to what extent they are familiar with the CLIL concept.